2023
DOI: 10.1007/s00170-022-10764-5
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid simultaneous laser- and ultrasonic-assisted machining of Ti-6Al-4V alloy

Abstract: The machinability of Ti-6Al-4V alloy has been a constant challenge in the industry, although the material is widely used in the aerospace and medical industries due to its mechanical properties, particularly its strength-to-weight ratio. The current research presents a hybrid laser- and ultrasonic-assisted machining (LUAM) technique to improve the machinability of Ti-6Al-4V alloy in a turning process. This is compared with ultrasonic-assisted machining (UAM), laser-assisted machining (LAM), and convectional tu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…The results showed that optimizing the laser power was crucial for machined surface roughness and machining efficiency, as shown in figure 22(b). Dominguez-Caballero et al [181] and Deswal and Kant [182] introduced a hybrid LUVAM technique to enhance the machinability of Ti-6Al-4V alloy in a turning process. The combined effect of the laser and ultrasonic assistance was particularly noticeable at the lowest cutting speed of 20 m min −1 , resulting in significant reductions in cutting forces in the tangential, radial, and feed directions, as shown in figure 22(c).…”
Section: Hybrid Nontraditional Energy-assisted Turningmentioning
confidence: 99%
See 1 more Smart Citation
“…The results showed that optimizing the laser power was crucial for machined surface roughness and machining efficiency, as shown in figure 22(b). Dominguez-Caballero et al [181] and Deswal and Kant [182] introduced a hybrid LUVAM technique to enhance the machinability of Ti-6Al-4V alloy in a turning process. The combined effect of the laser and ultrasonic assistance was particularly noticeable at the lowest cutting speed of 20 m min −1 , resulting in significant reductions in cutting forces in the tangential, radial, and feed directions, as shown in figure 22(c).…”
Section: Hybrid Nontraditional Energy-assisted Turningmentioning
confidence: 99%
“…(b) Surface roughness generated at various laser powers [180]. (c) Comparison of cutting forces in a single run [181]. (d) Comparison of cutting force and tool wear progression [184].…”
Section: Hybrid Nontraditional Energy-assisted Drillingmentioning
confidence: 99%
“…The ultrasonic vibration-assisted laser-assisted turning (UVLAT) technology has been proven to achieve the lowest cutting force for the tangential, radial, and feed force components. When compared to conventional turning (CT), ultrasonic-assisted turning (UAT), and laser-assisted turning (LAT), LUAM technology reduces the cutting forces in the tangential, radial, and feed directions by 70.1%, 59%, and 43%, respectively [ 218 ]. Figure 15 displays a chart comparing the cutting forces of these four processes in the tangential, radial, and feed directions.…”
Section: Hybrid Machining Of Sicp/almentioning
confidence: 99%
“…The higher damage on the machined surface was observed during the UVLAT process than that of the CT process (figure 5) and the reason was explained in section 3.4 which corelates well with the surface roughness. Kim et al and Dominguez-Caballero et al also reported higher surface roughness during the UVLAT process when compared with the CT process [26,28]. According to them, higher machining temperature during the UVLAT process led to higher heat affected zone with severe thermal damage, resulting in higher damage on the machined surface and higher surface roughness for the UVLAT process than the CT process.…”
Section: Surface Roughnessmentioning
confidence: 99%
“…Dominguez-Caballero et al explored machining forces, machining temperature, and surface roughness during the simultaneous application of ultrasonic vibration and laser energies in the turning process for Ti6Al4V alloy. Lower machining forces, higher machining temperature, and lower surface roughness were observed during the hybrid machining process in comparison to the CT process [28].…”
Section: Introductionmentioning
confidence: 99%